The relationship between cognitive ability and teaching performance in higher education in Malaysia using longitudinal and cross-sectional designs - Affezah binti Ali (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
The current research looks at the relationship between cognitive ability and teaching performance in higher education in Malaysia using longitudinal and cross-sectional designs. The objective was to examine the relationship between cognitive ability and teaching performance in longitudinal (Study 1) and cross-sectional (Study 2) designs. The result of linear regression analysis found that there was a significant positive correlation between cognitive ability and teaching performance for both designs study. However, the variance comparison between longitudinal and cross-sectional design showed that longitudinal design yielded a stronger relationship. The advantage and disadvantages of both designs had been discussed in discussion section. This current study also shows that cognitive ability can be an important measure for personnel selection in educational sector in Malaysia based on the adequate validity shown in both longitudinal and cross-sectional designs.